An assessment of collaborative research in corporate sustainability - Maitreyee Das; Abhishek Dutta; Gautam Dutta (Social Sciences and Humanities Open)
Corporate sustainability has emerged as an important domain of study as business and academia are increasingly recognizing the inter-relationship among business activities, societal well-being, and environmental protection. As concerns about climate change, social equity, and ethical business practices have intensified, researchers across various disciplines have increasingly collaborated to explore and address these complex challenges. This paper presents a bibliometric analysis of scholarly publications on the topic of corporate sustainability to deliver a detailed analysis of the status of the topic starting from the year 1995 when the first climate conference happened in Berlin to this date. In the process, this paper explored 2504 published papers documented in Scopus and Web of Science. Results obtained from the analysis show an exponential growth of publications on the topic, particularly after 2010. The study identifies the key contributors in corporate sustainability research in terms of the most productive authors, institutions, journals, and countries and also highlights less researched sub-domains under it. This can provide insightful directions to future researchers in this field. Our findings also suggest that, though the number of publications increased manifold, cross-country research collaboration has remained minimal. There is a need for more case study-based research papers that bring out sustainability success stories from developed nations with relatively higher SDG (Sustainable Development Goal) scores to set benchmarks for the rest of the world.